Viabilidade econômica de uma usina de beneficiamento de resíduos da construção civil no município de Campo Mourão, PR - Silva, Júlia Castro da (2023)
Beneficiation plants represent a viable alternative to prevent and reduce the impacts resulting from improper disposal of Construction and Demolition Waste (CDW), implementing measures that facilitate its management and allow for commercialization. This study aimed to evaluate the economic feasibility of implementing a CDW Beneficiation Plant in the municipality of Campo Mourão, Paraná, Brazil. To achieve this, a literature review was conducted, covering topics related to construction and demolition waste, beneficiation processes, the functioning of a beneficiation plant, investments, costs, revenues, and financial indicators. Based on geometric population projections for Campo Mourão and considering the per capita generation of CDW, waste generation was estimated for the next 10 years. Using these values, the demand for a plant with a processing capacity of 8 tons per hour was identified. Investment and cost values were projected, along with revenues from waste reception and the sale of recyclable aggregates. To assess economic viability, balance values for each year were evaluated, as well as the cumulative cash flow over the analysis horizon. The project was unable to generate sufficient financial returns to cover initial investments. The negative Net Present Value (NPV), an Internal Rate of Return (IRR) of only -8%, well below the Minimum Attractive Rate (MAR) of 20.75%, and a negative Return on Investment (ROI) of -77.54% indicate that the project is not economically attractive.Therefore, it was concluded that investing in the CDW Beneficiation Plant would not be financially viable. It would be prudent to explore other alternatives, such as a plant that receives waste from neighboring municipalities or consider different investment options to create a more attractive financial scenario.